2016
DOI: 10.1161/jaha.116.003634
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varying Hemodynamic and Vascular Conditions on Fractional Flow Reserve: An In Vitro Study

Abstract: BackgroundThe aim of this study was to investigate the impact of varying hemodynamic conditions on fractional flow reserve (ratio of pressure distal [Pd] and proximal [Pa] to stenosis under hyperemia) in an in vitro setting. Failure to achieve maximal hyperemia and the choice of hyperemic agents may have differential effects on coronary hemodynamics and, consequently, on the determination of fractional flow reserve.Methods and ResultsAn in vitro flow system was developed to experimentally model the physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
(92 reference statements)
0
16
0
Order By: Relevance
“…CT-derived fractional flow reserve, FFR) against a controlled in vitro forward flow gold standard. (31) Using 3D printed coronary-like vessels, which were fabricated using a clear rigid material (Veroclear, Stratasys), Kolli et al showed that FFR decreased as a function of aortic pressure. This relationship was established using a set of idealized 3D printed vessels with systematically placed stenotic regions that varied from 30% to 70%, resulting in absolute decreases in FFR of 0.03 to 0.2, respectively.…”
Section: Cardiovascular Applicationsmentioning
confidence: 99%
“…CT-derived fractional flow reserve, FFR) against a controlled in vitro forward flow gold standard. (31) Using 3D printed coronary-like vessels, which were fabricated using a clear rigid material (Veroclear, Stratasys), Kolli et al showed that FFR decreased as a function of aortic pressure. This relationship was established using a set of idealized 3D printed vessels with systematically placed stenotic regions that varied from 30% to 70%, resulting in absolute decreases in FFR of 0.03 to 0.2, respectively.…”
Section: Cardiovascular Applicationsmentioning
confidence: 99%
“…Because 3D printing models more accurately replicate the cardiovascular anatomy, the clinical applications have been focused on 'anatomy and function. ' Kolli et al [62] verified the impact of varying hemodynamic conditions on fractional flow reserve in an in vitro setting using 3D printing models. Maragiannis et al [63] demonstrated that patient-specific models using fused dual-material could replicate both the anatomic and functional properties of severe degenerative aortic valve stenosis.…”
Section: Future Directionsmentioning
confidence: 99%
“…22,25,26 Previous in vitro studies using idealized 3D printed coronary phantoms have indicated a dependence on FFR with increasing aortic pressure, making this adjustment in the 3D printed phantoms a necessary step toward replicating physiological conditions. 16 Figure 4(a) shows the setup of the phantoms within the flow loop and Fig. 4(b) shows the phantom setup within the CT gantry.…”
Section: Flow Experimentationmentioning
confidence: 99%
“…15 Previous research has shown the use of 3D printing to create coronary phantoms with stenosis; however, these phantoms were idealized and made out of rigid materials that do not replicate the compliance of vasculature. 16 Recently, 3D printing has been utilized to create patient-specific coronary phantoms that have been successfully used for flow measurements. [17][18][19] Despite a limited number of commercial polymers that are available for 3D printing, these phantoms have been demonstrated to approximately replicate the mechanical properties of vasculature.…”
Section: Introductionmentioning
confidence: 99%